Mexican New York : transnational lives of new immigrants - Smith, Robert C., 1964- (University of California Press, 2006)
Drawing on more than fifteen years of research, Mexican New York offers an intimate view of globalization as it is lived by Mexican immigrants and their children in New York and in Mexico. Robert Courtney Smith's groundbreaking study sheds new light on transnationalism, vividly illustrating how immigrants move back and forth between New York and their home village in Puebla with considerable ease, borrowing from and contributing to both communities as they forge new gender roles; new strategies of social mobility, race, and even adolescence; and new brands of politics and egalitarianism. Smith.